Intra-year employment instability and economic well-being among urban households: Mitigating effects of the social safety net. (May 2023) - Cai, Julie Y.; Wimer, Christopher; Berger, Lawrence; Maury, Matthew
Highlights: Stably nonemployment is most strongly associated with low income and poverty but not material hardship. Unstably employed households, particularly those that experience only job losses are more likely to have material hardship than consistently employed households. The safety net as a whole appears to be more effective for nonworking households than for unstably working households. In-kind transfers appear more important for unstably employed households, particularly those that are single-adult headed households facing job losses. Cash transfers effectively buffer against the negative impact of stably nonemployment. Abstract: Labor market structures and job characteristics have changed in the United States over the last few decades – often making work more unpredictable. Employment instability, or job churning, may have distinct consequences for households' economic well-being. Meanwhile, American social policies have shifted from cash-based benefits toward in-kind and work-conditioned programs. Yet, we know little about how social programs buffer the financial hardships imposed by economic shocks due to job churning. This paper harnesses novel data collected at 3-month intervals to study the associations between household members' employment trajectories and (1) household income packages, (2) poverty status, and (3) material hardships, paying particular attention to whether government benefit receipt buffers against the adverse financial consequences of unstable employment. We find that consistent unemployment is most strongly associated with low income and poverty but not material hardship. Unstably employed households, particularly those that are single-adult headed households and experienced only job losses are significantly more likely to experience material hardship than consistently employed households. Our results also suggest that cash transfers effectively buffer against the negative impact of persistent unemployment, while in-kind transfers appear more important for unstably employed households, particularly those that are single-adult headed households. Together, these results highlight the roles and extent of impacts of cash, in-kind benefits, and the tax system, which can inform future policy recommendations in an age of high levels of economic insecurity.